Design and analysis of robust fuzzy logic maximum power point tracking based isolated photovoltaic energy system. Issue 9 (24th July 2020) - Asif, Rao Muhammad; Ur Rehman, Ateeq; Ur Rehman, Saif; Arshad, Jehangir; Hamid, Jamshaid; Tariq Sadiq, Muhammad; Tahir, Sohaib
Summary: Photovoltaic (PV) energy is highly promising because of its renewable, green, and environment‐friendly nature. In this article, the design and analysis of an isolated PV system using a push‐pull converter with a fuzzy logic‐based maximum power point tracking (MPPT) algorithm is presented. Furthermore, DC‐DC converters, along with intelligent controllers fed with MPPT algorithms, are used to ensure the maximum extraction of incident energy. The proposed methodology utilizes fuzzy logic MPPT techniques based on an isolated push‐pull boost converter to optimize the power output of PV modules, as well as to achieve isolation and high DC gain for DC/AC inversion. This work also presents a single‐phase inverter with fuzzy logic close loop control analysis with LCL filter design. A Canadian solar panel of 250 W is assumed in this research work, which has an open circuit voltage 59.9 V, short circuit current 5.49 A at 25°C temperature, and 1000 W/m 2 irradiance. The voltages are tracked, through the MPPT algorithm. These voltages represent a boost to 340 V DC through push‐pull boost converter and are inverted up to 220 V AC through fuzzy logic voltage source inverter. In addition, a unipolar switching technique is used to remove the total harmonic distortion under linear load. The proposed methodology is simulated in MATLAB/Simulink. The simulation results verify that the proposed methodology can efficiently track the MPPT. Finally, the hardware prototype of the proposed system has been experimentally validated. Abstract : In this article, the design and analysis of an isolated photovoltaic system using push‐pull converter with the fuzzy logic‐based maximum power point tracking algorithm is presented. The proposed methodology has been simulated in MATLAB/Simulink. Its hardware prototype has also been experimentally validated.